Raw materials for the ceramics industry from norte de santander. I. Mineralogical, chemical and physical characterization (2016)
This paper examines the main characteristics of a clay used for manufacturing ceramic construction parts in the metropolitan area of San José de Cúcuta. The research was conducted using a sample of reddish clay of the Guayabo formation from the Zulia region in Norte de Santander. The material was ground by dry process and the suitable procedure for the preparation for the development of characterization analysis was performed as X-ray diffraction (XRD), X-ray fluorescence (XRF), particle sizes by dry sieving and technical 152H hydrometer. Their clay/quartz relationship, plasticity and behaviour in the process of drying and firing were determined. The forming process used was extrusion. The research results showed that the material is suitable for making structural and coating products for floors and walls, in addition to shedding excellent properties for manufacturing refractory products.